Faktor yang Memengaruhi Perilaku Konsumtif pada Perspektif Mental Accounting: Studi Penerima Bansos Orang Asli Papua - Munzir Munzir; Rosdinaman Budi; Satria Lintang Rachmadana; Anggun Srimeylani Palamba; Yohan Kondororik (Program Studi Akuntansi Unimuda Sorong, 2025)
Purpose: This study aims to examine the factors influencing the consumptive behavior of social fund recipients in Papua through the mental accounting framework. Specifically, it investigates the effects of framing and labeling, perception, spending decisions, and self-control on consumptive behavior. Methodology/approach: This study employed a quantitative survey approach. Data were collected from 70 social fund recipients in Papua selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS 28, preceded by classical assumption tests and simultaneous and partial hypothesis testing. Findings: The results show that framing and labeling, perception, spending decisions, and self-control simultaneously have a significant effect on consumptive behavior, with an F-value of 148.441 and a significance value of 0.000. The R² value of 0.901 indicates that the four variables explain 90.1% of the variation in consumptive behavior. Partially, only self-control has a significant effect on consumptive behavior, with a t-value of 22.448 and a significance value of 0.000, while framing and labeling, perception, and spending decisions have no significant individual effects. Practical implications: These findings highlight the importance of strengthening self-control in managing social assistance funds. Social assistance programs should be accompanied by financial management education and self-regulation interventions to promote more effective utilization of assistance funds. Originality/value: This study contributes to the behavioral finance literature by applying the mental accounting perspective to explain consumptive behavior among social fund recipients in Papua through the integration of cognitive, perceptual, spending decision, and self-control factors.